Foundation literature in sociological approaches - Samia BENRAMDHANE (Social Sciences Journal, 1970)
This study addresses the subject of conceptual connotations of the institution inthe context of the sociological approach, because the concept is today witnessing asubstantial intellectual changes imposed by the nature of what is seen incommunities of social and economic transformations as a result of the accumulationof Tribal Research, it confirmed the literature of contemporary regulatory andstudies it. For this study it aims to monitor the most important sociologicalapproaches that dealt with the evolution of the enterprise concept that accompaniedthe beginnings of the emergence of sociology as a discipline autonomous from otherdisciplines of social sciences, and this is the basis of approaches intellectualsociological classic to modern approaches sociological that contributed toregeneration in handling intellectual and theoretical and systematic interpretation ofthe institution and principles, in order to stability. In addition to the detection of themost important changes between disparate approaches in the sociologicalinterpretation of the concept of the institution.